Continuous pH monitoring in wounds using a composite indicator dressing — A feasibility study. Issue 6 (September 2019) - Nischwitz, S.P.; Bernardelli de Mattos, I.; Hofmann, E.; Groeber-Becker, F.; Funk, M.; Mohr, G.J.; Branski, L.K.; Mautner, S.I.; Kamolz, L.P.
Highlights: A bionanocellulose dressing was chemically functionalized with a pH indicator dye. Elegant and continuous pH monitoring of wounds can be performed. The developed product has excellent spatial and temporal resolution. The relevant pH range of 7–10 is covered. Abstract: Purpose: Modern burn care strives for new means to guarantee optimised wound healing. Several studies have shown a correlation between the pH value in a (burn) wound and successful wound healing. A multitude of devices to monitor pH is available, all requiring direct wound contact and removal of the dressing for pH monitoring. The aim of this feasibility study was to create a sterile and easy to handle method for pH monitoring while simultaneously using an advanced wound dressing. Materials and methods: Dressing sheets of biotechnologically generated nanofibrillar cellulose (epicite hydro ) were chemically functionalised with the indicator dye GJM-534. pH-donors with increasing pH were subsequently applied to the created indicator dressing. To investigate temporal resolution and continuous monitoring we used circular pH-donors with different pH (7 and 10) and decreasing diameters that were placed on another dressing sheet. Clinically relevant spatial resolution was checked by a wound bed simulation with small areas (8 mm) of higher pH (10) on a field of lower pH (7) and vice versa. Results: The indicator dressing showed a gradual colouring from yellow to dark orange with increasing pH in steps of 0.3. After conversion of digital pictures to greyscale values, a sigmoidal distribution with a p K a -value of 8.4 was obtained. A ring-like pattern with alternating colour change corresponding to the pH was observed in the continuous monitoring experiment and the wound bed simulation delivered excellent local resolution. Conclusion: Since the pH of a (burn) wound can have a significant influence on wound healing, a pH indicator was successfully linked to an advanced, temporary, alloplastic wound dressing material. We were able to show the possibility of pH monitoring by the dressing itself. Additional testing, including studies with large case numbers for optimisation are necessary before clinical implementation.